A Phenomenological Study of Fruit Pricing in Jakarta in the Context of a Harmonious Balance of Interests Among Suppliers, Vendors, and Buyers - Rousilita Suhendah; Ivan Kanel; Elsa Imelda; Darwis said; Syarifuddin (Cv. Syntax Corporation Indonesia, 2026)
Pricing practices in traditional markets are often understood from economic perspectives that emphasize cost calculations, market mechanisms, and profit maximization. However, everyday trading activities demonstrate that pricing decisions are also influenced by social relationships, moral considerations, and the sustainability of interactions among economic actors. This study aimed to explore the meaning of pricing experiences among papaya traders in Jakarta and to understand how prices function as a mechanism for balancing the interests of suppliers, traders, and buyers. This study employed a qualitative approach using Husserl’s transcendental phenomenological method. Data were collected through in-depth interviews with five purposively selected papaya traders in West Jakarta who had direct experience in determining selling prices. The data were analyzed using phenomenological stages, including noema, epoche, noesis, intentional analysis, and eidetic reduction. The findings reveal that traders do not interpret prices merely as instruments for generating profit but as social mechanisms that maintain supply continuity, buyer acceptance, and business sustainability. Pricing decisions reflect trust-based relationships with suppliers, efforts to offer acceptable prices to consumers, and strategies to sustain livelihoods. This study develops the concept of Harmony of Interests in Pricing, which explains that price formation integrates economic, social, and moral dimensions. The study concludes that pricing practices in traditional trade represent a form of social accountability that supports sustainable economic relationships among suppliers, traders, and buyers.